Plasmodium knowlesi Infection in Humans, Cambodia, 2007-2010 - Nimol, Khim; Sovannaroth, Siv; Saorin, Kim; Mueller, Tara; Fleischmann, Erna; Balbir, Singh; Paul Cliff, Simon Divis; Steenkeste, Nicolas; Duval, Linda; Bouchier, Christiane; Duong, Socheat; Ariey, Frederic; et al. (NationalCenter for Biotechnology Information, U.S. National Library of Medicine, 2011)
Two cases of Plasmodium knowlesi infection were identifi ed in humans in Cambodia by 3 molecular detection assays and sequencing. This fi nding confi rms the widespread distribution of P. knowlesi malaria in humans in Southeast Asia. Further wide-scale studies are required to assess the public health relevance of this zoonotic malaria parasite.